An Evo-Devo perspective on ever-growing teeth in mammals and dental stem cell maintenance - Renvoisé, Elodie; Michon, Frederic (Frontiers in Physiology, 2014)
A major challenge for current evolutionary and developmental biology research is to understand the evolution of morphogenesis and the mechanisms involved. Teeth are well suited for the investigation of developmental processes. In addition, since teeth are composed of hard-mineralized tissues, primarily apatite, that are readily preserved, the evolution of mammals is well documented through their teeth in the fossil record. Hypsodonty, high crowned teeth with shallow roots, and hypselodonty, ever-growing teeth, are convergent innovations that have appeared multiple times since the mammalian radiation 65 million years ago, in all tooth categories (incisors, canines, premolars and molars). A shift to hypsodonty, or hypselodonty, during mammalian evolution is often, but not necessarily, associated with increasingly abrasive diet during important environmental change events. Although the evolution of hypsodonty and hypselodonty is considered to be the result of heterochrony of development, little has been known about the exact developmental mechanisms at the origin of these morphological traits. Developmental biologists have been intrigued by the mechanism of hypselodonty since it requires the maintenance of continuous crown formation during development via stem cell niche activity. Understanding this mechanism may allow bioengineered tooth formation in humans. Hypsodonty and hypselodonty are thus examples of phenotypic features of teeth that have both impacts in understanding the evolution of mammals and holds promise for human tooth bioengineering.